Fostering international students' sense of belonging and perceived social support through a semester-long experiential activity. (December 2020) - Caligiuri, Paula; DuBois, Cathy L.Z.; Lundby, Kyle; Sinclair, Elizabeth A
We tested whether a semester-long classroom experiential activity designed to foster international and domestic student social interaction increases international students' sense of belonging and perceived social support. Two studies were conducted testing the effectiveness of this experiential activity which was based on the theoretical underpinnings of how social attachment is formed. The first study was a controlled experiment with freshmen university students. When compared to the control group, the students participating in the experiential activity had an increased sense of belonging and perceived social support by the end of the semester, especially when they had lower levels of openness at the onset of starting college. The second study was a longitudinal study conducted with graduate students. The results found that students had an increase in their sense of belonging and perceived social support. These studies suggest that semester-long classroom experiential activities designed to foster international and domestic student social interaction can foster international students' sense of belonging and social support.